2013
DOI: 10.1111/ina.12069
|View full text |Cite
|
Sign up to set email alerts
|

Fine and ultrafine particle emissions from microwave popcorn

Abstract: This study characterized fine (PM2.5 ) and ultrafine particle (UFP, diameter < 100 nm) emissions from microwave popcorn and analyzed influential factors. Each pre-packed popcorn bag was cooked in a microwave oven enclosed in a stainless steel chamber for 3 min. The number concentration and size distribution of UFPs and PM2.5 mass concentration were measured inside the chamber repeatedly for five different flavors under four increasing power settings using either the foil-lined original package or a brown paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…context, note that prior studies have reported that the use of a gas stove and the heating of a steel pan can produce 10 12 −10 13 particles per event; cooking popcorn in a microwave oven was reported to produce 10 10 −10 11 particles. 4,37,38 Liu et al 28 measured the particle production from natural mosquito repellents with similar ozone exposures as in the present study and found total particle production in the range 10 9 −10 11 particles, depending on the amount of product applied. Both of the products in this study with more than 10 9 total emitted particles are formulated or fragranced with a known secondary aerosol precursor, tea tree oil or lavender scent.…”
Section: Environmental Science and Technologysupporting
confidence: 68%
“…context, note that prior studies have reported that the use of a gas stove and the heating of a steel pan can produce 10 12 −10 13 particles per event; cooking popcorn in a microwave oven was reported to produce 10 10 −10 11 particles. 4,37,38 Liu et al 28 measured the particle production from natural mosquito repellents with similar ozone exposures as in the present study and found total particle production in the range 10 9 −10 11 particles, depending on the amount of product applied. Both of the products in this study with more than 10 9 total emitted particles are formulated or fragranced with a known secondary aerosol precursor, tea tree oil or lavender scent.…”
Section: Environmental Science and Technologysupporting
confidence: 68%
“…The total removal rate λ was determined by measuring particle concentration decay after the cooking finished. 32 With the results of air change rate a, the total removal rate λ, concentration C in,p (t 0 ), and room volume V, the nonlinear fitting of the indoor particle concentration increasing curves based on eq 2 was conducted to obtain the emission rate S p with Origin 9.0.0 (OriginLab Corp., Northampton, MA, USA).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The air change rate a was measured via the CO 2 -decay method. The total removal rate λ was determined by measuring particle concentration decay after the cooking finished …”
Section: Methodsmentioning
confidence: 99%
“…Furan is also formed through heating food. In recent years, special attention has been gained by the formation of 2,3‐butanedione (diacetyl) from microwave popcorn (Zhang et al., ). Saturated and unsaturated aldehydes from C3 onwards are formed by the thermal decomposition of linolenic acid (Belitz et al., ).…”
Section: Sources Of Vvocsmentioning
confidence: 99%